Appropriateness and Cost of Prophylaxis Stress Ulcer for Inpatient in the Internal Medicine Department in a Government Hospital: A Cross-Sectional Study - Octavia, Mega; Maziyyah, Nurul; Fauziyah, Rima Nurul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Guidelines from the American Society of Health-System Pharmacists (ASHP) 1999 prohibit acid-suppressing therapy for stress ulcer prophylaxis (SUP) in patients who are not critically ill. Stress ulcer prophylaxis is not recommended in non-ICU patients with <2 risk factors. Inappropriate use of SUP can increase costs for patients. This study aims to evaluate the use and the cost of SUP. This research was a non-experimental observational study with a cross-sectional approach. Data was collected retrospectively using the consecutive sampling method with a random sampling technique on the medical records of inpatients in the internal medicine ward of Sleman Regional Public Hospital from January to December 2020, totaling 340 samples. The results showed that proton pump inhibitors were the most widely used acid-suppressing drugs, with 45.8%. Furthermore, the histamine-2 receptor antagonist was 42.6%, the sucralfate group was 7.4%, and the antacid group was 4.2%. Of 340 patients, 57 (16.8%) were in the proper indication based on the guidelines, and 283 (83.2%) were under the wrong indication for SUP. They were using SUP with the proper indication so that the therapy could save treatment costs by Rp. 19,933,582. There was a high prevalence of inappropriate SUP prescriptions among inpatients in the internal medicine department; if these drugs were given with the appropriate indications, they could save more on the prophylaxis cost. Clinician pharmacists should develop an effective intervention strategy to reduce inappropriate SUP drugs.